Reductive sequestration of chromate by hierarchical FeS@Fe0 particles. (1st October 2016) - Du, Jiangkun; Bao, Jianguo; Lu, Chenghang; Werner, David
Abstract: Nanoscale Fe 0 (nFe 0 ) can detoxify Cr(VI)-bearing wastewater and groundwater, but rapid passivation is a negative factor for large-scale remediation applications. In this study, a magnetic FeS@Fe 0 hybrid material was fabricated by immobilization of iron sulfide (FeS) onto Fe 0 particles to improve the Cr(VI) removal capacity. The solid characterization confirmed that Fe 0 particles were encapsulated by amorphous iron monosulfide. The Cr(VI) uptake by FeS@Fe 0 hybrid particles was found to follow pseudo-second-order rate kinetics, and the Langmuir isotherm was most appropriate to describe Cr(VI) sorption. Meanwhile, the FeS@Fe 0 hybrid particles showed a much higher efficiency towards Cr(VI) sequestration compared to individual nFe 0 . Moreover, the results of batch experiments with various adsorbent doses indicated that the reactivity of FeS@Fe 0 varies with different FeS-to-Fe 0 molar ratios. The reaction rate constants for Cr(VI) removal first increased with an increasing FeS-to-Fe 0 ratio from 0/1 to 1/9, and then decreased for the FeS-to-Fe 0 ratio increased further 1/5 or 1/3. For environmental parameters, there was a negative effect of increasing the solution pH and dissolved oxygen on Cr(VI) removal. Furthermore, a mechanistic analysis revealed that Cr(VI) reduction occurred predominantly at the solid-liquid interface, and that Fe(II) regenerated from FeS@Fe 0 corrosion may account for 52% of the Cr(VI) reduction, while electrons from Fe 0 and FeS account for the rest. After treatment, Cr(VI) was completely transformed and immobilized as solid Fe-Cr hydroxide precipitates, thus avoiding secondary contamination. The FeS@Fe 0 hybrid material has a better potential for treating Cr(VI)-bearing wastewater than nano Fe 0 . Graphical abstract: Highlights: A novel FeS@Fe 0 material with hierarchical structure was fabricated. FeS@Fe 0 showed much higher reactivity than individual nFe 0 towards Cr(VI) sequestration. The coverage of FeS could accelerate multi-electron transfer from Fe 0 core to sorbed Cr(VI). Cr(VI) was completely converted to Cr(III) and immobilized in the form of Fe-Cr hydroxides.